Exploring the relationship between genetic polymorphisms and cancer in the Bangladeshi population (Journal of Bangladesh Academy of Sciences, 2025)
Since the completion of the Human Genome Project two decades ago, genetic polymorphisms in human DNA have gained significant attention for their role in diseases, particularly cancer. Cancer susceptibility studies have examined Single Nucleotide Polymorphisms (SNPs) across various genes, but populations such as Bangladeshis have remained underrepresented in this field of research. This review consolidates all 54 studies on cancer-related genetic polymorphisms in the Bangladeshi population, focusing on genetic factors involved in cancer progression, and 5 more studies on treatment toxicity association. A comprehensive search of online literature databases was conducted to identify studies specifically conducted on Bangladeshis, and  these  studies  are  organized by  cancer  type.  Various  genotyping techniques,  including  PCR-RFLP,  T-ARMS-PCR,  TaqMan  Assay,  and Sanger sequencing, were employed to detect genetic associations, all of which are discussed. Genes most frequently studied include TP53, XRCC1, CDH1, IL17A, and RAD51, with the TP53 rs1042522 polymorphism being the most investigated SNP. The review also identifies cancers such as blood, esophageal,  bladder,  hepatocellular  and  liver  cancer  as  understudied. Importantly, SNPs in genes such as MTHFR and GSTP1 were found to influence  chemotherapy-related  toxicities.  This  review  provides  a comprehensive overview of cancer polymorphism studies conducted on this population,  highlights  the  current  scope  of  research,  and  identifies opportunities  for  further  exploration.  It  emphasizes  the  potential  for discovering unique Bangladeshi polymorphisms, which could lead to more tailored cancer diagnosis and treatment approaches.J. Bangladesh Acad. Sci. 49(1); 1-20: June 2025